Description of a New Salamander of the Genus Onychodactylus from Shikoku and Western Honshu, Japan (Amphibia, Caudata, Hynobiidae) - Yoshikawa, Natsuhiko; Matsui, Masafumi; Tanabe, Shingo; Okayama, Takehito (Zootaxa, 2013)
Recent phylogenetic studies using mtDNA and allozymes clarified the presence of multiple distinct genetic lineages in the Japanese clawed salamander, Onychodactylus japonicus, of which two from northern regions of the country have already been described as new species. Based on morphological analyses of the remaining genetic lineages, we describe the lineage from Shikoku Island and Chugoku Mountains of western Honshu, in western Japan, as a new species, Onychodactylus kinneburi sp. nov. It belongs to the O. japonicus complex and is morphologically similar to O. japonicus (sensu stricto), but is distinguishable from all the other members of the complex by sharply defined yellowish-orange dorsal stripe on black ground color, lack of dark marking on chest, whitish ventrum, comparatively large body size, and relatively narrow head, usually with 19 presacral vertebrae, 13 costal grooves, and relatively smaller number of vomerine tooth series. The new species occurs exclusively in Shikoku Island, but is sympatric with O. japonicus in Chugoku Mountains.